Correlation of In Vivo and In Vitro Phase Transitions of Membrane Lipids in Escherichia coli - Overath, P. (1970)
A double mutant of Escherichia coli unable to synthesize or degrade unsaturated fatty acids can incorporate fatty acids with various hydrocarbon chain structures into the membrane phospholipids. The temperature characteristic of three physiological properties of cells grown with different fatty acids (growth, respiration, and efflux of thiomethylgalactoside) is compared with the physical properties of the isolated phosphatidylethanolamines in monolayers at an air-water interface. Breaks in the temperature characteristic of the properties measured in vivo correspond to phase transitions in the lipid films from a liquid-expanded to a condensed form. It is concluded that a liquid-like state of the lipid phase is required for proper membrane function.